Changes of power-velocity relationship in volleyball players during an annual training cycle - Busko, K. (Human Movement, 2009)
Purpose. The aim of the study was to follow the changes of maximal power output and power-velocity relationship in male volleyball players during an annual training cycle. Basic procedures. The study was conducted on six first-league volleyball players: age 25.0 ± 5.3 years, body height 195.2 ± 7.2 cm and body mass 91.2 ± 14.7 kg. Force-velocity and power-velocity relations were determined from five maximal cycle ergometer exercise tests, 10 s each, with increasing external loads amounting to 2.5, 5.0, 7.5, 10.0 and 12.5% of body weight, respectively. There were 2-min breaks between the tests. Maximal power output was computed from power-velocity curves. Maximal power output and power-velocity relationships were determined before the preparatory period (I), after the first competitive season (II) and after the second competitive season (III). Main findings. Significant increases occurred in the maximal power output from 12.80 ± 0.79 (preparatory period) to 13.11 ± 0.94 (after the first competitive season) and 13.44 ± 0.62 W·kg-1 (after the second competitive season). The mean optimal velocity (vo) increased non-significantly from 122.2 ± 16.1 rpm (I) to 129.2 ± 14.9 rpm (II), and decreased non-significantly during the second competitive season (119.5 ± 18.5 rpm). Conclusions. In the annual training cycle under study a statistically significant increase of the power output with the external load of 7.5% of body weight was noted. The relative maximal power output increased significantly after the second competitive season as compared with the measurement before the preparatory period. The optimal velocity changed insignificantly in the entire annual training cycle.